The Problem of Physical Punishment and Its Persistence: The Potential Roles of Psychoanalysis: An Introduction to the Section. Issue 1 (1st January 2020) - Holinger, Paul C.
ABSTRACT: Physical punishment is a complex topic. Might psychoanalysis, child/adolescent analysis, and developmental theory and research provide further understanding of the underlying causes, the resulting psychopathology, and potential solutions? In this section, we explore various intrinsic and extrinsic perspectives in an attempt to better appreciate the controversies surrounding physical punishment and its persistence.